2009
DOI: 10.1007/s10509-009-0205-5
|View full text |Cite
|
Sign up to set email alerts
|

Charged fluid sphere in bimetric general theory of relativity

Abstract: Static and spherical symmetric solutions of the field equations in the bimetric general theory of gravitation are obtained for perfect and anisotropic charged fluids under the assumption that the physical metric admits a one-parameter group of conformal motion. All solutions are matched to the Reissner-Nordstrom metric and possess positive energy density larger than the stresses, everywhere within the sphere. The solution agrees with Einstein's general relativity for a physical system comparable to the size of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…In the framework of bimetric gravity, the solution for spherically symmetric self-gravitating anisotropic matter distribution was investigated by Khadekar & Kandalkar (2004) and that solution agrees with the Einstein's GRT for a physical system compared to the solar system size of universe. A charged fluid was also studied in BGTR (Kandalkar & Gawande 2010). Recently, Grigorian et al (2018) have shown that the masses for superdense compact objects in bimetric theory can be essentially larger compared to the objects in GTR depending on the value of the bimetric parameter.…”
Section: Introductionmentioning
confidence: 99%
“…In the framework of bimetric gravity, the solution for spherically symmetric self-gravitating anisotropic matter distribution was investigated by Khadekar & Kandalkar (2004) and that solution agrees with the Einstein's GRT for a physical system compared to the solar system size of universe. A charged fluid was also studied in BGTR (Kandalkar & Gawande 2010). Recently, Grigorian et al (2018) have shown that the masses for superdense compact objects in bimetric theory can be essentially larger compared to the objects in GTR depending on the value of the bimetric parameter.…”
Section: Introductionmentioning
confidence: 99%